Experimental Investigation to Evaluate the Effective Moisture Diffusivity and Activation Energy of Cassava (Manihot Esculenta) under Convective Drying - Waramit, Pathiwat; Krittacom, Bundit; Luampon, Ratinun (Applied Science and Engineering Progress, 2022)
Investigation of effective moisture diffusivity (Deff) and activation energy (Ea) of cassava were conducted under convective drying at temperature and velocity of 60, 70, and 80 °C, and 1.0, 1.5, and 2.0 m/s, respectively. In the experiment, cassava was sliced into 3 mm-thickness and dried under given conditions until mass was saturated. Deff and Ea were described by Fick’s second law and Arrhenius-type equation, respectively. The experimental results indicated that the increase in Deff was significantly affected by increasing the hot air temperature and velocity. The slope method was used to calculate average Deff, and results were found to range from 3.83 × 10–9 – 9.86 × 10–9 m2/s. The Ea was found to decrease with an increase in hot air velocity, ranging from 21.23– 24.92 kJ/mol. Additionally, Moisture content (Mw) and Drying rate (DR) were also used to describe the drying kinetics. From the experimental results, Mw and DR decreased with an increase in drying time. DR increased with an increase in temperature and velocity, causing rapid decrease in Mw and drying time to reduce. The highest DR was found to be 0.55 gwater/min at a temperature of 80 °C and velocity of 2.0 m/s.